Graphene ground states - Friedrich, Manuel; Stefanelli, Ulisse (Zeitschrift für Angewandte Mathematik und Physik, 2018)
Graphene is locally two-dimensional but not flat. Nanoscale ripples appear in suspended samples and rolling up often occurs when boundaries are not fixed. We address this variety of graphene geometries by classifying all ground-state deformations of the hexagonal lattice with respect to configurational energies including two- and three-body terms. As a consequence, we prove that all ground-state deformations are either periodic in one direction, as in the case of ripples, or rolled up, as in the case of nanotubes.
CRIS-Team Scopus Importer:2021-10-21
Keywords: Graphene; Ground states; Nonflatness; Periodicity; Three-dimensional structures